2023
DOI: 10.3390/pharmaceutics15061656
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Nanoformulations for Quercetin Delivery

Abstract: Quercetin (QUE) is a flavonol that has recently received great attention from the research community due to its important pharmacological properties. However, QUE’s low solubility and extended first-pass metabolism limit its oral administration. This review aims to present the potential of various nanoformulations in the development of QUE dosage forms for bioavailability enhancement. Advanced drug delivery nanosystems can be used for more efficient encapsulation, targeting, and controlled release of QUE. An o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 180 publications
0
7
0
Order By: Relevance
“… 38 Studies have indicated that quercetin is soluble in alcohol and lipids, suggesting that quercetin may need to be administered through modified dosage forms, such as the use of nanocarrier systems, to improve its effectiveness and bioavailability in the treatment of arthritis and gouty arthritis. 39 Research findings indicate that eburicoic acid exhibits properties of an antioxidant and possesses anti-inflammatory effects. 40 Eburicoic acid has an obvious anti-inflammatory effect by inhibiting the activation of PI3K/Akt/NF-κB signaling pathway, 41 furthermore, it possesses the ability to suppress xanthine oxidase activity, leading to low uric acid levels.…”
Section: Discussionmentioning
confidence: 99%
“… 38 Studies have indicated that quercetin is soluble in alcohol and lipids, suggesting that quercetin may need to be administered through modified dosage forms, such as the use of nanocarrier systems, to improve its effectiveness and bioavailability in the treatment of arthritis and gouty arthritis. 39 Research findings indicate that eburicoic acid exhibits properties of an antioxidant and possesses anti-inflammatory effects. 40 Eburicoic acid has an obvious anti-inflammatory effect by inhibiting the activation of PI3K/Akt/NF-κB signaling pathway, 41 furthermore, it possesses the ability to suppress xanthine oxidase activity, leading to low uric acid levels.…”
Section: Discussionmentioning
confidence: 99%
“…A suitable approach that could overcome those problems is using nanocarriers that, targeting inflammation, allow the release of the drug locally, reducing side effects. There are multiple investigations where not only ‘classical synthetic drugs’ but “natural products” have been formulated using nanotechnology to treat different conditions such as cancer, cardiovascular diseases, or inflammation ( Hesari et al, 2021 ; An et al, 2023 ; Hussain et al, 2023 ; Tomou et al, 2023 ; Zandieh et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite their healthful properties, ingesting phenolic compounds in orally does not provide a sufficient concentration for systemic therapeutic effects due to their low solubility in water, poor absorption, and fast metabolism [9]. This problem has been solved by creating various composite pharmaceuticals from phenolic compounds using different methods (cyclodextrin coatings, simple emulsions, lipid nanoparticles, or liposomes [10][11][12][13]) to ensure the stabilization of polyphenols. The genus Tagetes (Asteraceae) is originally from the Americas, but some of its species, such as Tagetes erecta and Tagetes patula, were introduced to European countries from India and North Africa in the 16th century and became naturalized there [14].…”
Section: Introductionmentioning
confidence: 99%